2006
DOI: 10.4012/dmj.25.538
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Elasticity on Gap Formation in a Lining Technique with Flowable Composite

Abstract: The purpose of this study was to investigate the effect of flowable composites as liners for direct composite restorations, with key focus on the elastic moduli of flowable and condensable composites. After treating the composite mold cavity surface with an adhesive system, one of the flowable composites was placed as a 1 mm-thick layer on the cavity floor and irradiated for 20 seconds. The rest of cavity was subsequently filled with a condensable composite and irradiated for 40 seconds. Gap formation at both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…Table 3 Statistical analysis results ratio of fillers as conventional composites, hence exhibiting much improved mechanical properties 1,21) . They can be used not only as lining 2,22) or repair materials, but also as a filling material. Since flowable composites can be applied to a variety of cavities, esthetic properties are hence expected of them.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 Statistical analysis results ratio of fillers as conventional composites, hence exhibiting much improved mechanical properties 1,21) . They can be used not only as lining 2,22) or repair materials, but also as a filling material. Since flowable composites can be applied to a variety of cavities, esthetic properties are hence expected of them.…”
Section: Discussionmentioning
confidence: 99%
“…16,18,24 Furthermore flowable composites and resin modified glass ionomer cements have been recommended as liners under resin composites to reduce potential microleakage, gap formation and recurrent caries. 14,[25][26][27] In this study we have investigated the extent to which endodontic access influences cuspal deformation and strain during direct restoration with a low shrink resin composite. Endodontic access was either confined within the occlusal floor of an MOD cavity or (as is common clinically) with the axial walls of dentine removed.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts at minimizing this problem have included the use of low shrink composites, 10 incremental placement 11 and the use of liners including glass ionomer, flowable composites and polyacid-modified resin composites. [12][13][14] The performance of direct resin composites for the restoration of root filled teeth has been investigated experimentally ever since posterior resin composite materials were first introduced [15][16][17] and clinically in both retrospective and prospective clinical studies. Despite the less favourable outcomes in comparison with cuspal coverage restorations reported in retrospective studies, 3,4 two randomised clinical trials found superior performance compared to amalgam restorations in terms of fracture resistance, but with a problem of recurrent caries.…”
Section: Introductionmentioning
confidence: 99%